DESTERRITORIALIZAÇÕES DO/NO TRABALHO: UMA NARRATIVA DE UMA TRABALHADORA EM DEVIR - Silva, Abigail Marinho da (2019)
We begin with the Grecian notion that ethics is an exercise in thought and reflection; with a reach far beyond a simplistic reproduction and application of rules or solutions from the past. The notion of universal morality is thus opposed, and this thesis conceives a collective from the sharing of diverse experiences. With the intention of producing a text that accesses lived experiences, narrative was used as a tool to bring out the good and the bad of human practices, encounters and lived experiences. In order to produce a research produced with COM and not ON, the narrative emerges as a device of knowledge of collective production, telling the story of experiences in the workplace, based on the assumption that work is an ethical exercise; as ethical as freedom itself. It is understood that work entails making decisions whilst confronting the diverse values of others; therefore, work is envisioned as a "dramatic use of self" for the purposes of this these. Through the dynamics of the narrative, it is possible for this dissertation to describe the essence of work in the context of Vitoria, Espirito Santo, Brazil, through the spoken memories of meetings held in a specific CRAS organization in said city turned into text. Through field logs and audio recordings, the data collected and scenes found in this dissertation trace work landscapes with characters, dialogues and practices, as well as the geosocial processes of deterritorialization. The story is told through the eyes of a character named, Amália, a conceptual persona who functions as an analytical device. [Através dela se faz possível contar os desafios do trabalhar, seja o trabalho em forma de conhecimento técnico na Proteção Básica Social ou em forma de pesquisa.] Amália is presented amidst the “lines of flight”, opening new paths to critique and stimulate the deautomatization of labor; she faces powerful conflicts, filled with debate and the exchange of ideas, eventually finding the breath to continue on, laboring.